Probing Risk of Default in the Market-Leading Islamic Banking Industry: During the Covid-19 Pandemic - Mehreen, M. (Springer Science and Business Media Deutschland GmbH, 2022)
This study aims to highlight the bankruptcy-related challenges and the reasons behind bank failures for the global Islamic banking industry, and to understand the expected impact of Covid-19 on the financial health of the Islamic banking industry. Moreover, the study shows that going bankrupt is a costly process that affects all stakeholders. Evidence shows that in the case of Islamic banking, a Shariah-based bankruptcy prediction model for apprehending the true bankruptcy prediction is over-sighted. It may further sour the existing uncertain situation for the Islamic banking industry with the additional unfavorable impact of Covid-19. As the subjected pandemic has badly affected the flow of the financial system worldwide, Islamic banking is not isolated. Therefore, efficient bankruptcy prediction models equipped with the latest micro and macro-economic factors are compulsory for the sustainability of the Islamic banking industry. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.